Measuring the Quality of Life Felda Residents in Iskandar Malaysia Based on Perception of Quality of Life Index - Yusoff, Wan Zahari Wan; Arshad, Ezhwan Nur (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Quality of life is a change in the society from a state that is considered unsatisfactory to a better condition which includes not only economic development but also involves various aspects such as social, psychological, cultural, political and environmental. The success of a placement can be measured by the improvement in the quality of life of the local residents. Iskandar Malaysia (IM) is a rapidly growing and developing area of which they are expected to contribute to the lives betterment of people in the economy and in the surrounding area as stated in the Comprehensive Development Plan for South Johor Economic Region. The question arises to what extent the IM development projects beneficial to the survival of the residents in the area as well to help improve the quality of life of the local residents in line with the current rapid development being carried out. Therefore, the main objective of this study is to determine the quality of life of Felda residents in Iskandar Malaysia using quality of life perception index. The research focused on the Felda population in Iskandar Malaysia based on the justification that they are the group of people who receive the most significant impact on the development of IM in the process of land acquisition and loss of shelter and habitat for future employment with the expectations of receiving a better life. IM perception Quality of life measurement model is determined based on the Malaysian Quality of Life Index. In addition, the measurement of quality of life through perception model was constructed to solicit comments from the locals. The research methodology is through the collection of primary data and secondary data from surveys and interviews and collecting data from the relevant agencies. The data were analyzed and the results showed that the quality of life of Felda residents in IM at moderate levels. Only two components are achieved at the satisfactory level namely transportation and housing.Â This study hopes to benefit the related parties who involve in the policy making in reviewing the existing policy towards a better development which will subsequently increase the level of quality of life of the local and native residents in IM.